ECONOMIC LAWS OF INFORMATION TECHNOLOGY DEVELOPMENT (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This article explores the economic laws governing the development of information technology (IT). The study highlights the key principles that drive innovation, growth, and competition in the IT sector. By examining historical trends, current practices, and future projections, the research elucidates the fundamental economic forces at play. The findings underscore the importance of market dynamics, investment patterns, and regulatory frameworks in shaping the IT landscape. Additionally, the article discusses the impact of technological advancements on productivity, employment, and economic growth.